The Influence of Service Quality, Customer Satisfaction, and Price on Customer Loyalty (Case Study on Santuy Coffee Shop in Tambun, Bekasi) - Dina Fitria Annuri; Andrian, Andrian; Dian Sudiantini (Jurnal Ekonomi, 2025)
This research aims to find out the influence of customer quality on customer loyalty, the influence of customer satisfaction on customer loyalty, the influence of price on customer loyalty, service quality, customer satisfaction, and price on customer loyalty (case study at the Santuy coffee shop in Tambun, Bekasi). This research uses an associative type of research with a quantitative approach, which is measured using the coefficient of determination method with SPSS 29.0. The research population was customers of the Santuy coffee shop in Tambun and the sample was determined using a non-probability sampling method with a sample size of 105 people. The data used is primary data, which was collected through a questionnaire. Hypothesis testing is carried out using the t test and f test. The results of this research prove that partially service quality influences customer loyalty, customer satisfaction influences customer loyalty, and price influences customer loyalty. Simultaneous test results of service quality, customer satisfaction and price influence customer loyalty at Warung Kopi Santuy Tambun, Bekasi.